Clearing the Cupboard: The Role of Public Relations in London Clearing Banks' Collective Legitimacy-Seeking, 1950–1980. (September 2014) - Reveley, James; Singleton, John
Abstract : This essay conceptualizes and historically documents a negle cted trade association function: legitimacy-seeking. It uses the Committee of London Clearing Bankers case to show how an association can, by using manipulative public relations techniques, fulfil that function for its members. To the circumstances that prevent rent-seeking associations from becoming industry level efficiency enhancers, the essay adds a new factor—a political legitimacy crisis. Through the Committee, the banks' leaders responded to such a crisis in the 1970s prompted by the threat of bank nationalization. The case yields the following generalizable point. When members are faced with an external legitimacy threat, a trade association, even one with a history of collaborative learning, can get stuck at the rent-seeking end of the associational spectrum. By morphing from a cartel into merely a vehicle for asserting its members' political legitimacy through instrumental public relations, this is just where the Committee remained on that continuum.